The incentives to adopt food safety standards: the example of approval and health certificate in the dairy cattle farming sector in Souk Ahras, Algeria. (2016) - Mamine, Fateh
This work presents a study conducted on the incentives to adopt food safety standards in the dairy cattle farming sector in Souk Ahras in Algeria. The state remains the main prescriber of food safety standards because of its socio-political legitimacy as a guarantor of public health. Here, all possible incentives to adopt food safety standards (including the institutional environment, the market and the farm's desire for internal efficiency) have been studied. This study shows that, despite its shortcomings, the institutional environment played a positive role in the adoption of food safety standards. The absence of differentiation by the safety quality led to a lack of market incentives (price). While the farms' search for internal economic efficiency remains of paramount importance in the alignment with the food safety standards. Any initiative to establish standards must be accompanied by mechanisms aiming at strengthening the external and internal incentives of the farm.